Psikologi Lingkungan: Pentingkah Untuk Dipelajari? - Ayu Gigih Rizqia; Ai Siti Patimah; Arundati Shinta (Jurnal Psikologi, 2024)
ABSTRACT The more advanced a civilization, the more pollution threatens human life. This is because progress also produces goods that are increasingly difficult to decompose in nature. However, pollution occurs more because of human behavior than technology. Behavior that does not care about the environment will worsen environmental quality. Advanced technologies can actually also produce ways to neutralize pollution. Unfortunately, technological advances in presenting machines that neutralize pollution tend to be slower than the formation of behavior. Therefore, it is necessary to think about children up to students need to study environmental psychology. Keywords: Pollution, Environmental Psychology.